Comprehensive Smart Mess Management Web Platform - Ahilya Kokare,; Aboli Ganeshkar,; Gouri Rajmane,; Seema Bagali,; Neha Gholave,; S. A. Hajare, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Mess Management System is an innovative software solution designed to automate the manual process of managing mess-related activities such, inventory management, and billing. The system is developed using PHP as the programming language and MySQL as the database management system. The primary objective of this system is to reduce the workload on mess staff, increase efficiency, and reduce errors in the mess management process. This research paper focuses on the design and implementation of the Mess Management System and its impact on college hostel mess management. This is a cost- effective, efficient, and user-friendly software solution that automates the manual mess management process. The system can be customized to cater to the specific needs of different institutions and can significantly reduce the workload on mess staff. The system's scalability, flexibility, and ease of use make it a promising solution for college hostel mess management. However, further research can be carried out to address the system's limitations, such as the need for regular maintenance and the requirement of technical expertise.
Keywords: Mess Management System; PHP; Mysql